Isolasi dan Uji Potensi Bakteri Pelarut Fosfat dari Rizosfer Tanaman Kopi Robusta (Coffea robusta) - Herlambang, Hari Inti; Himawan, Achmad; Kristalisasi, Elisabeth Nanik (Program Studi Agroteknologi INSTIPER, 2025)
Nutrient elements are very important for robusta coffee plants, but the availability of these nutrients in acidic soil (pH less than 5.5) or alkaline soil (pH greater than 8) is limited, as phosphorus (P) becomes bound by iron (Fe), aluminum (Al), and calcium (Ca), making it unavailable to plants. Therefore, phosphate-solubilizing bacteria are needed to convert unavailable phosphorus into available phosphorus. The purpose of this study was to identify the presence of phosphate-solubilizing bacteria in the rhizosphere of robusta coffee plants from Glagaharjo Village, Kepuharjo Village, and Umbulharjo Village, as well as to isolate and test their potential as phosphate-solubilizing bacteria. The method used in the study was an observational method presented in descriptive form. The descriptive writing includes information about the sampling location (temperature, humidity, sunlight intensity, altitude), procedures for isolating phosphate-solubilizing bacteria, macroscopic observations, microscopic observations, phosphate solubilization potential testing, catalase testing, and oxidase testing. The results of the study found 45 bacterial isolates from the three Villages. However, analysis of phosphate-solubilizing bacteria showed that only 16 isolates were suspected to be phosphate-solubilizing bacteria, potentially capable of solubilizing phosphate, as indicated by clear zones formed when cultured on Pikovskaya agar medium. Based on the characterization results, phosphate-solubilizing bacteria were found in each of the sample locations: Location 1 (Glagaharjo Village), Location 2 (Kepuharjo Village), and Location 3 (Kepuharjo Village, Cangkringan Subdistrict, Sleman Regency). The identified bacterial genera were Azotobacter and Pseudomonas, and all isolates tested positive in catalase and oxidase tests.